2017
DOI: 10.1016/j.jimonfin.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity shocks and real GDP growth: Evidence from a Bayesian time-varying parameter VAR

Abstract: We examine the dynamic impact of liquidity shocks resonating in stock and housing markets on real GDP growth. We fit a Bayesian time-varying parameter VAR model with stochastic volatility to US data from 1970 to 2014. GDP becomes highly sensitive to house market liquidity shocks as disruptions in the sector start to emerge, yet more resilient to stock market liquidity shocks throughout time. We provide substantial evidence in favour of asymmetric responses of GDP growth both across the business cycle, and amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
4
4
0
Order By: Relevance
“…As the actual real GDP growth rate fell by 2.887% and 5.280% in 2008 and 2009 respectively, illiquidity shocks to ILR t account for 18.563% of the variation in real GDP growth. This result is close to that reported in Ellington, Florackis, and Milas (), where stock market illiquidity shocks explained 17% of the overall variation in GDP growth during the Great Recession. Similar results are found for illiquidity shocks to italicILRtitalicSmall, and the overall contribution of illiquidity shocks to italicILRtitalicLarge on real GDP growth reductions is much smaller than ILR t and italicILRtitalicSmall.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As the actual real GDP growth rate fell by 2.887% and 5.280% in 2008 and 2009 respectively, illiquidity shocks to ILR t account for 18.563% of the variation in real GDP growth. This result is close to that reported in Ellington, Florackis, and Milas (), where stock market illiquidity shocks explained 17% of the overall variation in GDP growth during the Great Recession. Similar results are found for illiquidity shocks to italicILRtitalicSmall, and the overall contribution of illiquidity shocks to italicILRtitalicLarge on real GDP growth reductions is much smaller than ILR t and italicILRtitalicSmall.…”
Section: Resultssupporting
confidence: 90%
“…In sum, according to our historical decomposition analysis, we found that illiquidity shocks explain quarterly economic activity in recession periods well in terms of magnitude and direction. This confirms the view of Chen, Chou, and Yen () that the dynamic link between recessions and stock market liquidity is strong, and it also echoes the findings in Ellington, Florackis, and Milas () and Ellington () that the magnitude of the effect of illiquidity shocks on real GDP is likely to be greater in recession periods.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations